Integrated model based on TPM and SMED to increase the efficiency in a plastic SME in Peru - Aratoma Choque, Salvatore Eugenio (2025)
For years, plastic has been used around the world due to its ability to acquire different shapes and textures, and its usefulness in applications such as medicine, food, agriculture, construction, and everyday objects. The great value of the plastics industry in Peru is reflected in its contribution to the industrial GDP of 4%, in addition to the 200,000 jobs that are generated annually. The objective of the research was to analyze and develop lean manufacturing tools to achieve a model that increases the efficiency of the production plan in an SME plastics company. Preventive maintenance, which is based on the review of machinery, devices, and equipment for their proper functioning, helped us increase OEE by 15% and reduce maintenance costs by 35%; while the SMED tool, which is based on the identification and measurement of machine changeover times, helped us reduce machinery preparation times by 41%. By achieving these improvements, which were analyzed through KPIs and simulated in the Arena program, an increase in the efficiency of the production process to 75% was obtained.